Life is an attitude : staying positive when the world seems against you - Chapman, Elwood N. (Crisp Pub. Menlo ParkUS, 1992)
Explores the essence of attitude and how staying positive improves all aspects of life. Shows how positive attitude contributes significantly to staying mentally healthy; and is an important factor in recovering physical wellness, in maintaining healthy relationships, and in enjoying one's job. Shares formula which positive people use for solving problems i.e. face the problem, make tough decisions, and never look back. Illustrates the five-step recovery process after a major setback, using the attitude pyramid.